Pengembangan Sistem Informasi Penggajian Karyawan PT. BPR Bumiasih - . Rinawati; Lydia Sitanggang (STMIK Mardira Indonesia, Bandung, 2014)
Service progress information system in the form of an application currently has a very important role. By having better information will facilitate the planning and control as well as making a decision within a company. With regard to the importance of information, especially in a company the data must be managed effectively to obtain the required information. PT BPR Bumi Asih NBP 27 office in this discussion is one of the companies that still perform data processing payroll manually. Therefore, it should be made software by adopting digital data processing, both in inputting data and in making statements to promote a service to the employees of the company. This application is developed by using the tools (tool) in data processing is the programming language Microsoft Visual Basic 6.0 with SQL Server 2000 database management These results indicate that the processing of computerized data tend to be younger and to have the results of the processing accuracy better than on using the manual method. In the event that any information, statements made tend to be younger and faster because it automatically according to the input data that has been entered at the beginning of the previous program. Keywords: system; information; payroll; employee